SOSIALISASI DAN IMPLEMENTASI APLIKASI SISTEM INFORMASI PENGELOLAAN PRODUKSI DAN PEMASARAN KERAJINAN ANYAMAN PANDAN PADA CV.ANYAMAN SEJATI - Iskandar, Riki; Arief Wisky, Irzal; Akhiyar, Dinul; Ade Putra, Teri (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Production management is one of the factors that determines the success of a business unit, because it can help determine the amount of raw materials, the production process and the results in the form of production results. In this condition, the use of production management can make it easier in terms of marketing, namely marketing pandanus woven handicraft products using the website, the use of website media in the marketing process can arouse the desire and interest of buyers or consumers to make transactions. So that with the application of a website-based marketing and production management information system application, it can help CV.Anyaman Sejati in a fast transaction process and display updated information